The effect of microfludization on characteristics and herbicidal potential of peppermint nanoemulsion on Amaranthus tricolor - Dimak, J.; Somala, N.; Laosinwattana, C.; Teerarak, M. (My University, 2024)
The natural herbicides are friendly environment and human health. Peppermint essential oil nanoemulsion was prepared by a high-energy emulsification method using microfluidization with a non-ionic surfactant Tween 60 and was used to inhibit germination of Amaranthus tricolor seeds. Droplet size of the nanoemulsion was reduced by increasing the pressure of microfluidization from 5000 to 20000 psi (from 130.2 to 69.8 nm). The highest pressure (20000 psi) found the smallest droplet size of the nanoemulsion that droplet size, PI value, and zeta potential were 69.8 nm, 0.277, and -44.17 mV, respectively. Also, each pressure formulation (5000, 10000, 15000, and 20000 psi) was evaluated for the pre-emergence herbicidal activities namely inhibition of seed germination and seedling growth, seed imbibition, and a-amylase of Amaranthus tricolor seed. The obtained results of herbicidal activities correlated with droplet size that the herbicidal activities increased when increasing the pressure of microfluidization. The nanoemulsion formulation of pressure at 20000 psi treatment solution showed the highest herbicidal activities. Thus, these results may promote the optimized nanoemulsion from peppermint essential oil using a microfluidization method as a natural pre-emergence herbicide to inhibit seed germination and seedling growth of A. tricolor.
Keywords: Essential oil; High-energy emulsification; Nanotechnology; Natural herbicide; Pre-emergence herbicide